Performance evaluation of radio resource schedulers in LTE and 5G NR two-tier HetNets - Busari, Sherif Adeshina (2022)
Network performance is critically dependent on the employed radio resource scheduler (RRS). The impact becomes even more significant in 5G ultra-dense networks due to the challenges of complicated base station distribution, user association, load balancing and inter-cell interference, among others. Using a combination of three popular schedulers (i.e., round robin (RR), proportional fairness (PF) and best channel quality indicator (BCQI)), we evaluate, in this work, the performance of two-tier heterogeneous networks where the different tiers employ the same or different RRSs. Using user throughput, cell capacity and system fairness as metrics, the results show that, on one hand, the average user throughput-system fairness tradeoff favours the use of the RR-PF combination (where the macrocell tier employs RR while the small cell tier uses PF). On the other hand, the BCQI-BCQI combination produces the highest network capacity, principally from about 5-10% of the total users, thereby sacrificing fair allocation of resources among the users. The results show that there is no globally optimal RRS combination across the metrics. As the mobile network operators have the freedom to deploy schedulers as they deem fit, the RRS combination can be selected to satisfy the performance targets of the respective use cases and deployment scenarios.